The metabolic syndrome: metabolic changes with vascular consequences - Wassink, A. M. J.; Olijhoek, J. K.; Visseren, F. L. J. (European journal of clinical investigation, 2007)
Despite criticism regarding its clinical relevance, the concept of the metabolic syndrome improves our understanding of both the pathophysiology of insulin resistance and its associated metabolic changes and vascular consequences. Free fatty acids (FFA) and tumour necrosis factor‐alpha (TNF‐α) play prominent roles in the development of insulin resistance by impairing the intracellular insulin signalling transduction pathway. Obesity is an independent risk factor for cardiovascular disease and strongly related to insulin resistance. In case of obesity, FFAs and TNF‐α are produced in abundance by adipocytes, whereas the production of adiponectin, an anti‐inflammatory adipokine, is reduced. This imbalanced production of pro‐ and anti‐inflammatory adipokines, as observed in adipocyte dysfunction, is thought to be the driving force behind insulin resistance. The role of several recently discovered adipokines such as resistin, visfatin and retinol‐binding protein (RBP)‐4 in the pathogenesis of insulin resistance is increasingly understood. Insulin resistance induces several metabolic changes, including hyperglycaemia, dyslipidaemia and hypertension, all leading to increased cardiovascular risk. In addition, the dysfunctional adipocyte, reflected largely by low adiponectin levels and a high TNF‐α concentration, directly influences the vascular endothelium, causing endothelial dysfunction and atherosclerosis. Adipocyte dysfunction could therefore be regarded as the common antecedent of both insulin resistance and atherosclerosis and functions as the link between obesity and cardiovascular disease. Targeting the dysfunctional adipocyte may reduce the risk for both cardiovascular disease and the development of type 2 diabetes. Although lifestyle intervention remains the cornerstone of therapy in improving insulin sensitivity and its associated metabolic changes, medical treatment might prove to be important as well.